2003
DOI: 10.1016/s0006-2952(03)00444-1
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of heme oxygenase-1 induction in carbon tetrachloride-induced hepatotoxicity

Abstract: Reductive metabolism of carbon tetrachloride (CCl(4)) is thought to cause lipid peroxidation which results in hepatic injury. Heme oxygenase-1 (HO-1) (EC 1.14.99.3), the rate-limiting enzyme in heme catabolism, is known to be induced by oxidative stress and to confer protection against oxidative tissue injuries. In this study, we examined the role of HO-1 induction in a rat model of CCl(4)-induced acute liver injury. CCl(4) treatment (1 mL/kg, intraperitoneally) produced severe hepatic injury in rats as reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
88
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 50 publications
11
88
0
3
Order By: Relevance
“…On the contrary, we observed that APAP-induced liver injury was markedly attenuated in CXCR2-KO mice with reduced neutrophil infiltration, compared with WT mice, in line with previous reports that CXCR2-KO mice exhibited attenuated neutrophil infiltration in various disease models [16][17][18][19][20][21][22][23][24][25][26][27]. Indeed, Hogaboam and colleagues [38] observed that only a low level of CXCR2 was expressed on untreated hepatocytes and that APAP could enhance CXCR2 protein expression only transiently with a time lag.…”
Section: The Roles Of Ho-1 In Apap-induced Liver Injurysupporting
confidence: 91%
See 2 more Smart Citations
“…On the contrary, we observed that APAP-induced liver injury was markedly attenuated in CXCR2-KO mice with reduced neutrophil infiltration, compared with WT mice, in line with previous reports that CXCR2-KO mice exhibited attenuated neutrophil infiltration in various disease models [16][17][18][19][20][21][22][23][24][25][26][27]. Indeed, Hogaboam and colleagues [38] observed that only a low level of CXCR2 was expressed on untreated hepatocytes and that APAP could enhance CXCR2 protein expression only transiently with a time lag.…”
Section: The Roles Of Ho-1 In Apap-induced Liver Injurysupporting
confidence: 91%
“…We further showed that a substantial portion of macrophages expressed CXCR2 and that macrophages were a major source of heme oxygenase (HO)-1, which exhibits protective activities for various liver injuries including APAP-induced liver injury [27][28][29][30]. Thus, the present study implied that CXCR2 has double-edged roles in APAP-induced liver injury, by regulating the recruitment of both iNOS-expressing neutrophils and HO-1-expressing macrophages.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…HO-1 overexpression could decrease apoptotic cell death by enhancing Bcl-2 and depressing caspase-3 expression (Wang et al, 2004). Induction of HO-1 by chemical inducers or selective overexpression is cytoprotective both in vitro and in vivo (Nakahira et al, 2003;Nath, 2006). In addition, it has been demonstrated that carbon monoxide might possess antiapoptotic properties (Brouard et al, 2000;Liu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of NF-κB in liver damage remains controversial. While it has been shown that NF-κB activation promotes cell survival in TNF-α-induced hepatotoxicity [26], studies have also indicated that NF-κB is an important regulator of numerous inflammatory mediators, several of which have been implicated in drug-induced hepatotoxicity [27,28]. On the basis of these observations, it is reasonable to speculate that Sparassis crispa may protect against hepatotoxicity by exerting anti-NF-κB actions.…”
Section: Discussionmentioning
confidence: 99%